PELAKSANAAN PRINSIP KEDAULATAN RAKYAT DALAM PEMILIHAN UMUM DI INDONESIA - , Taufik Firmanto, Prof. Dr. Sudjito, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study proposed to answer two fundamental questions concerning the implementation of the popular sovereignty principles in the general election in Indonesia, namely, first, how the implementation of the principle of popular sovereignty in the general election in Indonesia since the 1955 general elections until the general election of 2009, secondly, how the ideal goal of elections in accordance with the principle of popular sovereignty in a democratic system in Indonesia. This research are empirical and non normative. The study was conducted to examine the way library materials in the form of books, journals, research reports and/ or secondary data discuss the implementation of the general election in Indonesia associated with the sovereignty of the people. Implementation of legislation (legal fact) which is arranging the elections in Indonesia are also treated as part of social and political realities in the life of the nation. From this study, the authors concluded that: the first application of the principle of popular sovereignty in the general election in Indonesia since 1955 until 2009, very dynamic. The enthusiasm of the people of Indonesia to follow the implementation of the elections as a means of popular sovereignty is not flat and without any problems, many factors that influence the dynamics of development in accordance with the surrounding statehood. A noble ideal of âelections as a means of popular sovereigntyâ is not as easy to say it. The author observes a wide gap between the concept of popular sovereignty as sollen das, das Sein with the realities and problems of the election as the embodiment of popular sovereignty in Indonesia. There are various obstacles to be overcome in order to actually generate the election of a democratic government. Embodiment of popular sovereignty in the general election and free and fair overflow should not ignore the present purposes are accommodated in the form of guarantee of proportionality and the degree of representativeness, the strengthening of representative institutions, as well as simplify the party system, strengthening the presidential system of government, political participation, and noted in particular Women's representation. Second, in a democracy the people's rights should be respected and upheld. Not justified the decision of the government that can harm people's rights, let alone a policy that aims to suppress the people in the interest of the ruler. In this case, by adhering to the basic philosophy of "democracy led by the inner wisdom of deliberations of representatives", the organization of elections as a means of implementation of the sovereignty of the people in Indonesia are not allowed out of the ideals and objectives of the establishment of a Government of Indonesia to protect the whole Indonesian nation and the entire homeland of Indonesia, promote the general welfare, the intellectual life of the nation, and participate in the establishment of a world order based on freedom, abiding peace and social justice as mandated by the constitution.